The Social Policy of the Prophet Muhammad as an Agent of Transformation of the Pre-Islamic Social Hierarchy - Najeb Mohamad Ali; Ishak Muniba; Jo Smith Clusmann; Naufal Mohamad Ali; Feigin Botzen (Yayasan Albahriah Jamiah Indonesia, 2026)
This article departs from the character of the social hierarchy of pre-Islamic Arab society, which was rigid and exclusive based on lineage, clan, economic status, and gender relations, as well as from the limitations of contemporary hadith and sirah studies, which are still predominantly normative-descriptive, so that they are inadequate in explaining the mechanisms of social change structurally and their implications for the development of hadith studies. This study aims to critically analyze the social policies of the Prophet Muhammad as an agent of transformation of social hierarchy through normative, institutional, and social-praxis dimensions, while also offering a socio-structural reading that is relatively underused in hadith studies. This study uses a qualitative approach based on a thematic-contextual analysis of social hadiths in a purposively selected corpus of canonical hadith books, proceeding through the stages of theme identification, categorization, and contextual interpretation, and is supported by socio-historical readings and a theoretical framework of social change. The results of the study indicate three main mechanisms: first, the deconstruction of lineage-based stratification through the principle of moral equality that negates genealogical superiority; second, the reconstruction of social structures through the inclusion of marginalized groups such as enslaved people and people experiencing poverty in a system of welfare distribution and equitable social relations; third, the institutionalization of inter-tribal solidarity through brotherhood, collective ethical regulation, and the strengthening of women’s roles in the socio-symbolic sphere. This transformation occurred systematically and continuously, resulting in a more egalitarian social order. These findings affirm the Prophet Muhammad as an agent of strategic social change and broaden the horizons of hadith studies toward contextual, relevant socio-structural analysis.